(untitled) (TAMADDUN NURI JURNALI, 2024)
The article discusses the peculiarities of dialectal somatic terms in the language of the Kazakhs of Karakalpakstan. Somatic terms are closely linked to national culture and traditions, providing information about the language of the local people and the history of their formation. The study of such somatic terms allows us to determine the cultural and historical territorial features of the language.